Evaluation of salt tolerance in turfgrass species of Peninsular Malaysia - Zulkaliph@Zulkifli, Noor Azwa (2013)
Demand for salt tolerant turfgrass species is increasing in Malaysia due to shortage of fresh irrigation water and salt water intrusion in seashore area. The aim of this research was to evaluate salinity tolerance of turfgrass species across Peninsular Malaysia. The specific objectives of this study were (i) to screen the salinity tolerance of local turfgrass entries in Peninsular Malaysia, (ii) to study the morphological and physiological responses of turfgrass species to salinity stress, and (iii) to evaluate the growth performance of salt tolerant turfgrass species in the field condition. Turfgrass species were collected from the coastal areas of Peninsular Malaysia. A total of 34 turfgrass entries were screened in the first experiment. This experiment was carried out in glasshouse and four different salinity levels [0 (control), 24, 48 (100% seawater), and 72 dS m-1] were used to irrigate the turfgrasses. All the entries of turfgrasses were grouped for salinity tolerance on the basis of shoot and root growth, leaf firing, turf colour index and turf quality. Regardless of the species or entries,increasing the salinity levels had increased the percentage of leaf firing, decreased turf colour index, turf quality, relative shoot growth and root growth. The most tolerant species group comprised of P. vaginatum (16)*, P. vaginatum ‘local’, Z. matrella, Z. japonica, C. dactylon ‘satiri’ , C. dactylon (9)* which were able to tolerate high levels of salinity (24 to 48 dS m-1). While, the least tolerant group were E. ophiuroides, P. notatum, A. compressus ‘cowgrass’, A. affinis, and A. compressus ‘pearl blue’ which were affected at salinity levels of 24 dS m-1. The morphological and physiological mechanisms for salt tolerant turfgrass species were studied in the second experiment. Based on the findings of first experiment, three most salt-tolerant species (P. vaginatum, Z. matrella and C. dactylon ‘satiri’) and one medium salt-tolerant turfgrass species (C. dactylon ‘tifdwarf’) were selected for this experiment. These species were subjected to five salinity levels (0, 12, 24, 36 and 48 dS m-1). Physiological data recorded in this experiment were chlorophyll concentration, leaf proline accumulation, relative water content, and mineral analysis of Na, N, P, K, Ca and Mg. Growth parameters (leaf firing, turf quality, turf colour index, shoot growth and root growth) were also determined. The presence of salt gland and root cortex structure were observed under scanning electron microscope (SEM). Growth responses and the physiological data had indicated that P. vaginatum, Z. matrella and C. dactylon ‘satiri’ were more salt tolerant than C. dactylon ‘tifdwarf’. Leaf proline concentration of all turfgrass species were sharply increased while chlorophyll concentration and relative water content (RWC) decreased in response to increasing the salinity level. The high salt tolerant turfgrass species (P. vaginatum, Z. matrella and C. dactylon ‘satiri’) were * Numbers in the brackets denote entry number as listed in Table 3.1 able to maintain the high level of chlorophyll content compared to C. dactylon ‘tifdwarf’. The P. vaginatum and Z. matrella have the ability to preserve osmotic adjustment indicated by relative water content and proline accumulation even at the highest salinity treatment (48 dS m-1). These species were less affected by salinity on selective uptake of saline ion (Na) uptake and with minimal interference of nutrient function and uptake (N, P, K, Ca and Mg) at high salinity levels. The SEM study revealed the presence of salt gland excretion in Z. matrella, C. dactylon ‘satiri’ and C. dactylon ‘tifdwarf’ leaves and it was one of the mechanisms operating for adaptation to salinity. The collapsed root cortex cells of C. dactylon ‘tifdwarf’ due to salinity stress were higher compared to other three species. The performances of three high salt tolerant species (P. vaginatum, Z. matrella and C. dactylon ‘satiri’) in the second experiment were then examined under field conditions. Five different salinity levels (0, 12, 24, 36 and 48 dS m-1) were applied to these species on daily basis. Eight parameters were recorded namely leaf firing, turf colour index, turf quality, shoot density, shoot growth, root growth, and root volume. It was found that P. vaginatum showed the highest performance on saline irrigation compared to Z. matrella and C. actylon ‘satiri’. The P. vaginatum showed least leaf firing (5%) with better turf quality (8.33 rating) and it was able to maintained good green colour (6.94 turf colour index) when irrigated with sea water (48 dS m-1). The root growth and root volume of this species was increased with the increasing salinity up to 24 dS m-1 compared to other two species. Salinity tolerance ranking of the tested species was found as: P. vaginatum > Z. matrella > C. dactylon ‘satiri’. From this study it may be concluded that P. vaginatum was the most salt tolerant species followed by Z. matrella and C. dactylon ‘satiri’. These turf grass species could be viable and cost effective, and they can be used as the alternative solutions for the problems of salt affected area.